Endometrial biopsy using a novak curette for the detection of endometrial pathology - Esteban-Habana, Ma. Antonia
Various methods have been developed to assess the presence of endometrial pathology in women with abnormal uterine bleeding. The use of curettage as the standard method of endometrial sampling is questioned. Endometrial biopsy is a safe alternative and the accuracy of biopsy using the novak curette is evaluated. The objectives of this study: 1. To determine the adequacy of specimens obtained from endometrial biopsy and curettage. 2. To determine the sensitivity, specificity, predictive values, accuracy and likelihood ratios of histology results obtained from endometrial biopsy with those obtained from curettage. 3. To determine the sensitivity, specificity, predictive values, accuracy and likelihood ratios of histology results obtained from endometrial biopsy and curettage with those obtained from available hysterectomy specimens. 4. And to compare adverse events and any difficulties encountered in both techniques. Criterion validation study done prospectively where endometrial biopsy was evaluated using an independent and blind comparison with a gold standard, the histology result from an endometrial curettage and when available, the hysterectomy specimen. The study was approved by the Committee on Research Implementation and Development of the College of Medicine and the Philippine General Hospital of the University of the Philippines. It was conducted at the Outpatient Section of the Department of Obstetrics and Gynecology of the Philippine General Hospital from June 1, 1998 to June 7, 1999. Four hundred thirty one consecutive patients with clinical indications for curettage who satisfied the following inclusion and exclusion criteria were included in the study.
The inclusion criteria were as follows: 1) clinical indication to undergo curettage; 2) written informed consent to undergo both endometrial biopsy and curettage; and 3) preoperative clearance if with medical illness. The exclusion criteria were 1) acute pelvic inflammatory disease; 2) bleeding disorders; 3) anemia; 4) pregnancy; and 5) profuse vaginal bleeding. All participants underwent an endometrial biopsy using the Novak curette immediately followed by endometrial curettage. An experienced pathologist, blinded to the method used, randomly examined the specimens. In cases where a hysterectomy was perfomed within 12 weeks from the procedure, the results of the biopsy and curettage were also compared to that of the hysterectomy specimen. Sensitivity, specificity, accuracy, positive and negative predictive values, prevalence and likelihood ratios were calculated. There were 431 participants with the majority presenting with abnormal uterine bleeding. Significantly more inadequate specimens were obtained after a biopsy than a curettage. A comparison of both techniques based on the diagnosis of abnormal endometrium, showed a sensitivity of 37.8 (95 CI: 24.21, 53.41), specificity of 98.7 (95 CI: 96.46, 99.57) and accuracy of 90.0 . Based on the diagnosis of uterine malignancies, the sensitivity was 83.3 (95 CI: 36.82, 99.04), specificity of 100 (95 CI: 98.93, 99.98) and accuracy of 99.7 . Likelihood ratios for a result that showed abnormal endometrium increased the post-test probability more than 6 fold. There was a significantly greater inability to insert the curette for the conventional curettage and likewise a greater need for cervical dilatation. One adverse event, that of uterine bleeding after curettage, was noted (0.2). The study does serial testing of biopsy and curettage and a lesion maybe removed by biopsy (false positive compared to curettage) or a lesion missed by both biopsy and curettage (false negative compared to hysterectomy). Since biopsy was done under anesthesia, one can not make any generalizations on patient acceptance. Endometrial biopsy is a useful diagnostic procedure for the detection of endometrial cancer. It is highly accurate but must be used with an understanding of its limitations. Post-endometrial biopsy curettage may be indicated in certain conditions.
Thesis (Master of Science in Epidemiology)--University of the Philippines Manila.
Keywords: Biopsy; Noval Curette -- Diagnostic use